Taking sides clashing views in business ethics and society - Newton, Lisa H. (McGraw-Hill, 2010)
Capitalism and the corporation; Current business issues; Human resources: the corporation and employees; Consumer issues; Global objectives; Environmental policy and corporate responsibility.